Pre-operative pressure pain thresholds do not meaningfully explain satisfaction or improvement in pain after knee replacement: a cohort study. Issue 1 (January 2019) - Leung, Y.Y.; Lim, Z.; Fan, Q.; Wylde, V.; Xiong, S.; Yeo, S.J.; Lo, N.N.; Chong, H.C.; Yeo, W.; Tan, M.H.; Chakraborty, B.; Bak-Siew Wong, S.; et al.
Summary: Objectives: Pain sensitization could be a risk factor for poor outcomes after knee replacement surgery (KR) for knee osteoarthritis (KOA). We aimed to evaluate the association between pre-operative central and peripheral pain sensitization measured using a digital pressure algometer and KR outcomes. Methods: Consecutive patients with severe KOA listed for KR were recruited. Sociodemographic and symptoms data were collected prior to surgery. Pre-operative pressure pain thresholds (PPTs) were measured using a digital pressure algometer at the index knee and forearm. Patient satisfaction at 6 and 12 months after KR was assessed using a 4-point Likert scale, and dichotomized to satisfied and dissatisfied to KR. Western Ontario and McMaster Universities Index (WOMAC) Pain and function was assessed. The associations between pre-operative PPTs with KR outcomes at 6 and 12 months were evaluated. Results: Of the 243 patients recruited, response rate at 6 and 12 months were 95.5% and 96.7%. The dissatisfaction rates were 8.2% and 5.1% at 6 and 12 months. There was no statistically significant association between pre-operative index knee or forearm PPTs and patient satisfaction. PPTs measured at the knee, but not the forearm, were weakly associated with change in the WOMAC pain score at 12 months, after adjustment for confounding factors. Conclusion: Pre-operative central sensitization, measured by handheld digital algometry, was not statistically significantly associated with satisfaction or change in pain after KR. Pre-operative peripheral sensitization was associated with change in pain symptoms after KR; however, this association was weak and unlikely to be a meaningful predictor of KR outcome in clinical practice.